PENSIONS AT RISK: INFORMALITY AND WITHDRAWALS THAT THREATEN PENSION SECURITY IN PERU - Gutiérrez Ayala, Jael Rossmery (2025)
The main objective of this article is to analyze the impact of labor informality, which currently affects the population. Taking into account data provided by the National Household Survey (ENAHO), in 2022, around 75.7% of workers were in the informal sector, resulting in approximately 13.4 million people and massive withdrawals from pension funds, this compromises long-term sustainability and puts the financial security of millions of Peruvians at risk in their old age. This research examines how these factors affect the coverage and viability of the pension system and proposes possible solutions to mitigate the negative effects of these problems. This research uses a mixed approach, combining quantitative and qualitative elements. In the quantitative approach, we use numerical and statistical data to demonstrate the impact of the crisis on the pension system. Meanwhile, in the qualitative approach, we analyze the problem from an interpretive perspective, exploring the causes and proposing solutions. Furthermore, it is basic and non-experimental in design. Information was collected from the following public entities: the National Institute of Statistics and Informatics (INEI), the Superintendency of Banking, Insurance, and Pension Funds (AFPs) (SBS). The following data collection tools were used: official reports, newspaper sources, academic studies (undergraduate and graduate theses), books, and current regulations. Finally, to improve the coverage and sustainability of the pension system, it is proposed to incentivize pension savings for informal workers with state subsidies and tax benefits. Furthermore, it is key to strengthen financial education to avoid premature withdrawals and establish a mixed system with a guaranteed minimum pension and greater protection for older adults without sufficient income.